2018
DOI: 10.1155/2018/7140902
|View full text |Cite
|
Sign up to set email alerts
|

Fluoride Variations in Rivers on the Slopes of Mount Meru in Tanzania

Abstract: This study reports the variations of fluoride ions in rivers on the slopes of Mount Meru in the northern part of Tanzania. More than 318 water samples were collected from Temi, Nduruma, Tengeru, and Maji ya Chai Rivers in both wet (mid-March and April) and dry (August) seasons. The samples were analyzed for fluoride levels using Ion Selective Electrode (ISE). The minimum and maximum average fluoride levels in the wet season were 0.24 ± 0.03 mg/l and 65.20 ± 0.03 mg/l, respectively, whereas the average lowest a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 14 publications
2
12
0
Order By: Relevance
“…Fluoride dissolution and availability seems to have correlated with the high pH of the water, indicating that the dissolution of fluoride influenced the pH. This finding is consistent with the observations Kitalika et al. (2018) , who observed a linear correlation when comparing fluoride and pH trends in rivers of Mount Meru, Tanzania.…”
Section: Resultssupporting
confidence: 90%
“…Fluoride dissolution and availability seems to have correlated with the high pH of the water, indicating that the dissolution of fluoride influenced the pH. This finding is consistent with the observations Kitalika et al. (2018) , who observed a linear correlation when comparing fluoride and pH trends in rivers of Mount Meru, Tanzania.…”
Section: Resultssupporting
confidence: 90%
“…In the Arusha volcanic region in northern Tanzania, around Mount Meru, several studies with focus on F⁻ concentration in surface water (Kilham and Hecky, 1973;Nanyaro et al, 1984;Kitalika et al 2018) and groundwater (Ghiglieri et al, 2012;Chacha et al, 2018;Makoba and Muzuka, 2019;Bennett et al, 2021) have been conducted. The studies found that the general groundwater chemistry is F⁻-rich NaHCO3 alkaline water.…”
Section: Introductionmentioning
confidence: 99%
“…The study area involved the foothills of the eastern and south west parts of Mount Meru which is part of the entire Pangani basin sub catchment located in the Nothern part of Tanzania sub catchment (Figure 1). 41 The natural vegetation in this area is typically tropical forest to savannah and topography is dominated by the Mount Meru volcanic cone of Pleistocene to recent origin. The local climate of the area is temperate Afro-Alpine with minimum and maximum daily temperature of 20.6 °C and 28.5 °C, respectively.…”
Section: Description Of Study Areamentioning
confidence: 99%